Objective and Subjective Assessment of the Sound Attenuation Efficiency Obtained by Custom Moulded Earplugs with Various Acoustic Filters – a Preliminary Study - GOŁEBIEWSKI, Roman; WICHER, Andrzej; DURAJ, Artur; KACZMAREK-KLINOWSKA, Milena; MRUGALSKA-HANDKE, Karina (Archives of Acoustics, 2022)
Background: Hearing loss caused by excessive exposure to noise is one of the most common health risks for employees. One solution for noise reduction is the use of hearing protectors, which is a very effective method for protecting hearing from the workplace noise. In order to obtain better attenuation efficiency, custom moulded earplugs can be equipped with a suitable acoustic filter. The effectiveness of the hearing protectors’ attenuation is based on real measurement of hearing thresholds for normal hearing people with and without hearing protectors. However, this is a time consuming process, and the obtained values are characterised by quite large inter-individual variability. The optimal solution is to measure the attenuation characteristics based on the objective method (without the presence of the subject), the results of which will be in accordance with the results of subjective tests. Therefore, the main purpose of the research in this work was to measure the attenuation characteristics of the self-designed custom moulded earplugs with and without acoustic filters through the use of subjective and objective methods, and to compare the results in terms of the research methods.Methods: Measurements of the acoustic attenuation obtained by custom moulded earplugs with designed F1, F2, and F3 acoustic filters (internal diameters dF1 = 1:25 mm, dF2 = 0:85 mm, and dF3 = 0:45 mm), as well as full insert earplugs (without any acoustic filters) were carried out using two methods: objective and subjective. The objective measurements were carried out in an anechoic chamber. The artificial head (High-frequency Head and Torso Simulator Brüel & Kjær Type 5128) was located at a distance of 3 m, directly opposite the loudspeaker. The test signal in the measurements was pink noise – in the frequency range up to 12.5 kHz and the level 85, 90, and 95 dB. The hearing protectors with and without acoustic filters were mounted in the Head and Torso Simulator which was connected with Pulse System Brüel & Kjær. Five normal hearing subjects participated in the subjective measurements. A pink noise signal was used for one-third octave bands: 125, 250, 500, 1000, 2000, 4000, and 8000 Hz. The attenuation value was defined as the difference (in dB) between the hearing threshold of the test signal with a hearing protector and the hearing threshold determined without a hearing protector.Results: The results of the objective method proved that in addition to the significant impact of frequency on the attenuation values, the type of filter used in custom moulded earplugs also had a significant effect. In addition, the results of the objective method showed that in the whole frequency range the highest attenuation values are shown by the full earplugs, achieving slightly above 45 dB for frequency of 8 kHz. The attenuation values obtained from subjective measurements also confirmed that both the frequency and type of filter significantly affect the attenuation values of the tested hearing protectors.Conclusions: The results of this study did not confirm the hypothesis that the measurement method had no significant effect on the attenuation characteristics of self-designed custom moulded earplugs with different types of acoustic filters. The largest differences in attenuation values between the type of measurement methods occur for the low frequency band (250 Hz) and for higher frequencies (4000 Hz mainly). The change of the internal diameter of the F1 filter from 1.25 mm to 0.85 mm (F2 filter) did not significantly affect the attenuationcharacteristics.